A Low Cost Wearable Medical Device for Vital Signs Monitoring in Low-Resource Settings - Muhammad Niswar; Muhammad Nur; Idar Mappangara (Institute of Advanced Engineering and Science, 2019)
Medical devices are often expensive, so people in low-income countries cannot afford them. This paper presents the design of a low-cost wearable medical device to measure vital signs of a patient including heart rate, blood oxygen saturation level (SpO2) and respiratory rate. The wearable medical device mainly consists of a microcontroller and two biomedical sensors including airflow thermal sensor to measure respiratory rate and pulse oximeter sensor to measure SpO2 and heart rate. We can monitor the vital signs from a smartphone using a web browser through IEEE802.11 wireless connectivity to the wearable medical device. Furthermore, the wearable medical device requires simple management to operate; hence, it can be easily used. Performance evaluation results show that the designed wearable medical device works as good as a standard SpO2 device and it can measure the respiratory rate properly. The designed wearable medical device is inexpensive and appropriate for low-resource settings. Moreover, as its components are commonly available in the market, it easy to assembly and repair locally.